2004
DOI: 10.1016/s1570-0232(04)00678-6
|View full text |Cite
|
Sign up to set email alerts
|

Chromatographic and electrophoretic methods for Lingzhi pharmacologically active components

Abstract: Lingzhi is the Chinese name given to the Ganoderma family of mushrooms, which was considered the most valuable medicine in ancient China and was believed to bring longevity, due to its mysterious power of healing the body and calming the mind. Today, Lingzhi is still widely revered as a valuable health supplement and herbal medicine worldwide, as studies (mostly conducted in China, Korea, Japan and the United States) into the medicinal and nutritional values of Lingzhi revealed that it does indeed contain cert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
76
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(77 citation statements)
references
References 0 publications
0
76
0
1
Order By: Relevance
“…Dai et al (1987) demonstrated the mitochondrial superoxide dismutase stimulating activity of Ganoderma. Recent reports also indicated the presence of vitamins C and E, as well as bcarotene and essential elements in various Ganoderma species (Huie and Di 2004). Pharmacological treatment using these antioxidant vitamins shown effectiveness in preventing oxidative stress and mitochondrial function during aging in individual cases (Ghosh et al 1996;Chinnery and Turnbull 2000;Marriage et al 2004;Navarro et al 2005).…”
Section: Body Weight (G)mentioning
confidence: 98%
“…Dai et al (1987) demonstrated the mitochondrial superoxide dismutase stimulating activity of Ganoderma. Recent reports also indicated the presence of vitamins C and E, as well as bcarotene and essential elements in various Ganoderma species (Huie and Di 2004). Pharmacological treatment using these antioxidant vitamins shown effectiveness in preventing oxidative stress and mitochondrial function during aging in individual cases (Ghosh et al 1996;Chinnery and Turnbull 2000;Marriage et al 2004;Navarro et al 2005).…”
Section: Body Weight (G)mentioning
confidence: 98%
“…These polysaccharides have been found able to stimulate the proliferations or enhance the activities of T lymphocytes [31], splenocytes [32], immunological effector cells (e.g., bone marrow cells, red blood cells, white blood cells, natural killer cells, T and B cells) [33]. The existence of selenium has also been identified in two types of polysaccharides isolated from Gls [40]. According to Gasser et al, this essential element acted as a mitogenic factor and thus was an indispensable supplement of serum-free media for CHO cell cultures [47].…”
Section: Effects Of Gls On Protein Productivitymentioning
confidence: 99%
“…The main active compounds of Gls extracted in boiled water are polysaccharides [40], researches on which have identified anticancer, immunostimulatory, immunomodulatory, and antioxidant activities [31][32][33]. To further explore the activity of Gls extract on CHO K1 cell growth in the context of serum inefficiency, a 6-well plate culture was carried out using the media #1, #2, #4, and #6 (shown in Table 1).…”
Section: Effects Of Gls On Cell Cyclesmentioning
confidence: 99%
“…The sulfated polysaccharides/glycoproteins are found to act as antitumor agents (36). More than 200 polysaccharides/ glycoconjugates have been isolated from Ganoderma lucidum, which is a well-known traditional Chinese medicine (37,38).…”
Section: Potential Functional Ingredients From Marine Productsmentioning
confidence: 99%